2020
DOI: 10.1159/000509671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic and Predicative Values of 8-Iso-Prostaglandin F2α as a Biomarker of Breast Cancer

Abstract: Background: Breast cancer (BC) is a commonly reported cancer that is widely prevalent among women. Its early detection improves patient survival and results in better outcomes. For diagnosis and follow-up care, tumor markers are one of the feasible investigations to be ordered. 8-Iso-prostaglandin F2α (8-iso-PGF2α) serves as a serum marker reflecting oxidative stress and subsequent damaging of DNA. In the present study, we aimed to evaluate both diagnostic and predictive values of 8-iso-PGF2α in BC patients. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This study also revealed that COVID-19 co-infected with malaria was the highest comorbidity recorded; this may be due to malaria being pandemic in the region coupled with fragile healthcare delivery and poor malaria control programs. In another study on factors which increase production of ROS such as malaria, Nour Eldin et al 44 reported increased lipid peroxidation and elevated level of 8-iso-PGF2α. Similarly, our research revealed significantly increased levels of 8-iso-PGF2α in COVID-19 co-infected with malaria compared to COVID-19 subjects without co-infection, lower levels of antioxidant vitamins were also noted among the co-infected group compared to COVID-19 naïve.…”
Section: Discussionmentioning
confidence: 97%
“…This study also revealed that COVID-19 co-infected with malaria was the highest comorbidity recorded; this may be due to malaria being pandemic in the region coupled with fragile healthcare delivery and poor malaria control programs. In another study on factors which increase production of ROS such as malaria, Nour Eldin et al 44 reported increased lipid peroxidation and elevated level of 8-iso-PGF2α. Similarly, our research revealed significantly increased levels of 8-iso-PGF2α in COVID-19 co-infected with malaria compared to COVID-19 subjects without co-infection, lower levels of antioxidant vitamins were also noted among the co-infected group compared to COVID-19 naïve.…”
Section: Discussionmentioning
confidence: 97%
“…8-Iso-prostaglandin F 2a (8-iso-PGF 2α ) serves as a serum non-invasive marker reflecting oxidative stress and subsequent damaging of DNA. The serum level of 8-iso-PGF 2α in the breast cancer patients (57.92 pg/mL) was significantly higher compared to those with benign tumors (18.89 pg/mL) (p < 0.001) [43].…”
Section: Prostaglandins In Breast Cancermentioning
confidence: 80%
“…In addition to promoting proliferation, further studies have shown that prostaglandin F2α (PGF2ɑ) can increase the invasion of carcinoma‐derived cells in colorectal cancer 120 . Additionally, it has been found that PGF2ɑ also has the potential as a breast cancer biomarker 144 . However, some PGs are considered to be antitumorigenic.…”
Section: Effects Of Signaling Fas On Cancer Cellsmentioning
confidence: 99%
“…120 Additionally, it has been found that PGF2ɑ also has the potential as a breast cancer biomarker. 144 However, some PGs are considered to be antitumorigenic. For example, prostaglandin D2 (PGD 2 ) has been reported to reduce pancreatic tumorigenesis.…”
Section: Cyclooxygenase Synthesis Pathwaymentioning
confidence: 99%